Dualistic nature of the object of intellectual property "industrial design" - Markova, Maria (Research Papers, 2018)
The problem of industrial design as an object of intellectual property is topical as a legal tool to protect product innovations and business identifiers due to the incomplete knowledge of its legal features and the opportunities to obtain economic benefits from its use in business.The aim of this study is to present legal regulation of the "industrial design" as an object in international and national regulation and the possibilities of protection of product decisions and of creative business identifiers such as advertising materials, documents, symbols and logos through the IP object "industrial design", their economic functions in the conditions of nowadays competitive market. The results of the research for a registration activity in industrial design in Bulgaria are presented according to the facts and data of the Bulgarian Patent Office, accompanied by analysis and recommendations to business.The study is carried out within a period of 1999-2017, as the author took into account the new Industrial Design Law since 1999, the own professional experience and the available information on the activity of Bulgarian natural and juridical persons – the creators of design solutions.As a result of the theoretical analysis and of the realized research, the author presents a conclusion that the object of IP ‘industrial design’ is a suitable legal tool for protecting small product innovations and business identifiers - design results with significant legal consequences for their owner on the competitive global market. Bulgarian business entities can use this kind of legal protection and this way it will be useful in terms of a barrier to prevent illegal copying and imitation, and for the purpose of better economic results.
Keywords: Intellectual property; Industrial design